LEVERAGING NATURAL DISASTERS FOR DIPLOMATIC OBJECTIVES IN INDONESIA AND TÜRKIYE IN 2023 TÜRKIYE’S EARTHQUAKES - Isnarti, Rika; Marnani, Christine Sri; Ramadhan, Iqbal; Kusumawardhana, Indra; Haridha, Frieska; Rudiany, Novita Putri (CV The Journal Publishing, 2024)
This research examines the concept of disaster diplomacy and its application in Indonesia and Türkiye, specifically focusing on the earthquake disaster in Türkiye in 2023. By analyzing how natural disasters are utilized in diplomatic strategies, this study sheds light on the role of disasters in shaping diplomatic relations. Data was collected through interviews with the National Agency for Disaster Countermeasures of the Republic of Indonesia and experts in disaster management and Indonesia-Türkiye relations. Library research and government reports were also utilized. The research findings indicate that Indonesia strategically employs disasters to enhance its disaster management capabilities and diplomatic relations. By utilizing disasters as an instrument, Indonesia advances its national interests, particularly in natural disaster resilience. On the other hand, Türkiye has successfully obtained international aid, including assistance from Indonesia, which aligns with its long-standing diplomatic goals. Türkiye effectively showcases the strength of its diplomatic practice. Through an exploration of these dynamics, this research contributes to a deeper understanding of how natural disasters intersect with diplomatic strategies in Indonesia and Türkiye. It sheds light on how disasters are utilized as tools for achieving national goals and enhancing diplomatic relations